A Hermeneutic Phenomenological Study On The Meaning Of Compliance Towards Jakim Halal Logo Requirements For Malaysian Halal Certified Food Manufacturers - Othman, Rosly (2011)
The globalisation of the world has significantly facilitated the international movement of food products between Muslim and non Muslim countries. Along with other Muslim countries in the world, Malaysia is also actively participating in the international trade of halal food. Within the halal food industry, this means that the Islamic authorities must be able to ensure the halal status of all food products available to Muslim consumers so that the needs of this population can be fulfilled. One way of doing this is through the use of JAKIM halal logo certification. Such action is a dynamic and increasingly prevalent model of halal status assurance.